Lung diffusion in a 14-day swimming altitude training camp at 1850 meters - Garcia, I.; Drobnic, F.; Galera, T.; Pons, V.; Viscor, G. (International Journal of Environmental Research and Public Health, 2020)
Swimming exercise at sea level causes a transient decrease in lung diffusing capacity for carbon monoxide (DLCO). The exposure to hypobaric hypoxia can affect lung gas exchange, and hypoxic pulmonary vasoconstriction may elicit pulmonary oedema. The purpose of this study is to evaluate whether there are changes in DLCO during a 14-day altitude training camp (1850 m) in elite swimmers and the acute effects of a combined training session of swimming in moderate hypoxia and 44-min cycling in acute normobaric severe hypoxia (3000 m). Participants were eight international level swimmers (5 females and 3 males; 17-24 years old; 173.5 ± 5.5 cm; 64.4 ± 5.3 kg) with a training volume of 80 km per week. The single-breath method was used to measure the changes in DLCO and functional gas exchange parameters. No changes in DLCO after a 14-day altitude training camp at 1850 m were detected but a decrease in alveolar volume (VA; 7.13 ± 1.61 vs. 6.50 ± 1.59 L; p = 0.005; d = 0.396) and an increase in the transfer coefficient of the lung for carbon monoxide (KCO; 6.23 ± 1.03 vs. 6.83 ± 1.31 mL·min-1·mmHg-1·L-1; p = 0.038; d = 0.509) after the altitude camp were observed. During the acute hypoxia combined session, there were no changes in DLCO after swimming training at 1850 m, but there was a decrease in DLCO after cycling at a simulated altitude of 3000 m (40.6 ± 10.8 vs. 36.8 ± 11.2 mL·min-1·mmHg-1; p = 0.044; d = 0.341). A training camp at moderate altitude did not alter pulmonary diffusing capacity in elite swimmers, although a cycling session at a higher simulated altitude caused a certain degree of impairment of the alveolar-capillary gas exchange.